COMPARISON OF NUTRITIONAL PATTERN AND USE BETWEEN COVID AND NON-COVID INTENSIVE CARE PATIENTS - Dr. Sanjith Saseedharan; Dr. Ganesh Shingade; Dr. Chandrima Pramanik; Dr. Malaika Panchal (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Nutrition is important for our immune system. The COVID-19 pandemic further supported this, as the hyper-catabolic state presented an extremely difficult challenge. Multiple studies have been conducted that demonstrate how crucial adequate nutrition is in COVID-19 patients. The study included 941 patients, of which 599 were diagnosed with COVID-19, and 342 were non-COVID patients. Scientific powder-based feeding formula was prescribed using the iNutrimon™ software. COVID-19 patients who tolerated oral feeds were given scientific enteral feeding formula and in non-COVID patients supplemental nutrition was added only if they did not achieve at least 50 % of the prescribed diet at the end of 72 hours. Towards the end of our study, we observed that COVID-19 patients had longer ICU stays and increased use of TPN and supplemental nutrition compared to non-COVID patients. The daily nutritional expenditure for COVID-19 patients was also higher than non-COVID patients. In conclusion, in comparison between COVID-19 patients and non-COVID patients, it was seen that in COVID-19 patients, there was an increased use of scientific feeding formulas and TPN. The majority of non-COVID patients were managed without TPN compared to COVID-19 patients. Further studies are needed to provide insight into the impact of scientific feeding formulas in the recovery of COVID-19 patients after discharge from the ICU.